Effect of an oral bivalent vaccine on immune response and immune gene profiling in vaccinated red tilapia (Oreochromis spp.) during infections with Streptococcus iniae and Aeromonas hydrophila - Monir, Md Shirajum; Mohd Yusoff, Md Sabri; Saad, Mohd Zamri; Amal, Mohammad Noor Azmai; Mohamad, Aslah; Sayuti, Mohamad Azzam; Md Yasin, Ina-Salwany (MDPI, 2022)
Streptococcosis and aeromonasis inflicted by Streptococcus iniae and Aeromonas hydrophila, respectively, have affected tilapia industries worldwide. In this study, we investigated antibody responses and explored the mechanisms of protection rendered by an oral bivalent vaccine in red tilapia following challenges with S. iniae and A. hydrophila. The results of specific IgM antibody response revealed that the IgM titers against S. iniae and A. hydrophila in the bivalent incorporated (BI) vaccine group were significantly higher (p < 0.05) than those in the bivalent spray (BS) vaccine fish and unvaccinated control fish throughout the experiment. Real-time qPCR results also showed that the gene expression of CD4, MHC-I, MHC-II, IgT, C-type lysozyme, IL-1β, TNF-α, and TGF-β remained significantly higher (p < 0.05) than that of the controls between 24 and 72 h post-infection (hpi) in both mucosal (hindgut) and systemic (spleen and head–kidney) organs of BI vaccinated fish. Furthermore, the highest relative expression of the TGF-β, C-type lysozyme, and IgT genes in the BI vaccinated group was observed in the challenged fish’s spleen (8.8-fold), head kidney (4.4-fold), and hindgut (19.7-fold) tissues, respectively. The present study suggests that the bivalent incorporated (BI) vaccine could effectively improve the immune function and activate both humoral and cell-mediated immunities in vaccinated red tilapia following the bacterial challenges.